Dynein-mediated apical localization of crumbs transcripts is required for Crumbs activity in epithelial polarity - Li, Zhouhua (The Rockefeller University Press, 2008)
Asymmetrical localization of transcripts coupled with localized translation constitutes an important mechanism widely deployed to regulate gene activity in a spatial manner. The conserved transmembrane protein Crumbs (Crb) is an important regulator of epithelial polarity. However, it remains unclear how Crb is targeted to the apical domain. Here, we show that the cytoplasmic dynein complex transports both Crb protein and transcripts to the apical domain of Drosophila melanogaster follicular cells (FCs). The crb 3′ untranslated region (UTR) is necessary and sufficient for the apical localization of its transcript and this apical transcript localization is crucial for crb function. In crb mutant FCs, Crb protein derived from transgenes lacking the 3′ UTR does not effectively localize to the apical domain and does not effectively restore normal epithelial polarity. We propose that dynein-mediated messenger RNA transport coupled with a localized translation mechanism is involved in localizing Crb to the apical domain to mediate epithelial apicobasal polarity and that this mechanism might be widely used to regulate cellular polarity.